Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Here is a detailed, step-by-step solution to find \(x^2 + \frac{1}{x^2}\) and \(x^4 + \frac{1}{x^4}\) given that \(x - \frac{1}{x} = 5\).
### Step 1: Square the given equation
Given:
[tex]\[ x - \frac{1}{x} = 5 \][/tex]
Square both sides of the equation:
[tex]\[ \left( x - \frac{1}{x} \right)^2 = 5^2 \][/tex]
Expand the left-hand side:
[tex]\[ x^2 - 2 \cdot x \cdot \frac{1}{x} + \left( \frac{1}{x} \right)^2 = 25 \][/tex]
Simplify:
[tex]\[ x^2 - 2 + \frac{1}{x^2} = 25 \][/tex]
### Step 2: Isolate \(x^2 + \frac{1}{x^2}\)
Add 2 to both sides to isolate the term we need:
[tex]\[ x^2 + \frac{1}{x^2} = 25 + 2 \][/tex]
[tex]\[ x^2 + \frac{1}{x^2} = 27 \][/tex]
### Step 3: Square the result to find \(x^4 + \frac{1}{x^4}\)
Next, we need to find \( x^4 + \frac{1}{x^4} \).
Square the equation we found in Step 2:
[tex]\[ \left( x^2 + \frac{1}{x^2} \right)^2 = 27^2 \][/tex]
Expand the left-hand side:
[tex]\[ x^4 + 2 \cdot x^2 \cdot \frac{1}{x^2} + \frac{1}{x^4} = 729 \][/tex]
Simplify:
[tex]\[ x^4 + 2 + \frac{1}{x^4} = 729 \][/tex]
### Step 4: Isolate \(x^4 + \frac{1}{x^4}\)
Subtract 2 from both sides to isolate the term we need:
[tex]\[ x^4 + \frac{1}{x^4} = 729 - 2 \][/tex]
[tex]\[ x^4 + \frac{1}{x^4} = 727 \][/tex]
### Summary
- The value of \( x^2 + \frac{1}{x^2} \) is \(27\).
- The value of \( x^4 + \frac{1}{x^4} \) is \(727\).
So, we have:
[tex]\[ x^2 + \frac{1}{x^2} = 27 \][/tex]
[tex]\[ x^4 + \frac{1}{x^4} = 727 \][/tex]
### Step 1: Square the given equation
Given:
[tex]\[ x - \frac{1}{x} = 5 \][/tex]
Square both sides of the equation:
[tex]\[ \left( x - \frac{1}{x} \right)^2 = 5^2 \][/tex]
Expand the left-hand side:
[tex]\[ x^2 - 2 \cdot x \cdot \frac{1}{x} + \left( \frac{1}{x} \right)^2 = 25 \][/tex]
Simplify:
[tex]\[ x^2 - 2 + \frac{1}{x^2} = 25 \][/tex]
### Step 2: Isolate \(x^2 + \frac{1}{x^2}\)
Add 2 to both sides to isolate the term we need:
[tex]\[ x^2 + \frac{1}{x^2} = 25 + 2 \][/tex]
[tex]\[ x^2 + \frac{1}{x^2} = 27 \][/tex]
### Step 3: Square the result to find \(x^4 + \frac{1}{x^4}\)
Next, we need to find \( x^4 + \frac{1}{x^4} \).
Square the equation we found in Step 2:
[tex]\[ \left( x^2 + \frac{1}{x^2} \right)^2 = 27^2 \][/tex]
Expand the left-hand side:
[tex]\[ x^4 + 2 \cdot x^2 \cdot \frac{1}{x^2} + \frac{1}{x^4} = 729 \][/tex]
Simplify:
[tex]\[ x^4 + 2 + \frac{1}{x^4} = 729 \][/tex]
### Step 4: Isolate \(x^4 + \frac{1}{x^4}\)
Subtract 2 from both sides to isolate the term we need:
[tex]\[ x^4 + \frac{1}{x^4} = 729 - 2 \][/tex]
[tex]\[ x^4 + \frac{1}{x^4} = 727 \][/tex]
### Summary
- The value of \( x^2 + \frac{1}{x^2} \) is \(27\).
- The value of \( x^4 + \frac{1}{x^4} \) is \(727\).
So, we have:
[tex]\[ x^2 + \frac{1}{x^2} = 27 \][/tex]
[tex]\[ x^4 + \frac{1}{x^4} = 727 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.